2010
DOI: 10.1002/jcla.20319
|View full text |Cite
|
Sign up to set email alerts
|

New generation IQ‐200 automated urine microscopy analyzer compared with KOVA cell chamber

Abstract: IQ-200 can perform accurate quantification of microscopic element in urine. However, automated techniques are not completely free of error. Therefore, by adopting an appropriate algorithm and combining the results with stript analysis and other laboratory tests allows further reduction of clinically important errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 12 publications
(11 reference statements)
2
21
0
1
Order By: Relevance
“…For instance, as carry-over was identified as a potential problem in some of the studies,15 20 23 24 the potential for significant carry-over should be part of the verification study. In the published studies, carry-over was non-existent or on such a small scale that it could not be of any consequence for the microscopy results,7 13 15 25 28 31 32 34 36 but with some analysers, even minimal carry-over could potentially affect the subsequent culture results 15 20 23 24. Various strategies have been suggested to reduce the potential impact of carry-over on bacterial cultures including increasing the number of rinsing cycles between specimens,15 taking aliquots for culture before the sample is processed for microscopy,15 20 23 24 regular disinfection of the sampling and mixing devices23 24 or performing the culture before the microscopy, though this last option denies the benefits of screening 23.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, as carry-over was identified as a potential problem in some of the studies,15 20 23 24 the potential for significant carry-over should be part of the verification study. In the published studies, carry-over was non-existent or on such a small scale that it could not be of any consequence for the microscopy results,7 13 15 25 28 31 32 34 36 but with some analysers, even minimal carry-over could potentially affect the subsequent culture results 15 20 23 24. Various strategies have been suggested to reduce the potential impact of carry-over on bacterial cultures including increasing the number of rinsing cycles between specimens,15 taking aliquots for culture before the sample is processed for microscopy,15 20 23 24 regular disinfection of the sampling and mixing devices23 24 or performing the culture before the microscopy, though this last option denies the benefits of screening 23.…”
Section: Discussionmentioning
confidence: 99%
“…How quickly the microscopy was performed was reported in some studies in relation to the collection time, and it varied greatly ranging between 1 hour,7 52 2 hours,8 20 32 47 59–61 64 3 hours,63 4 hours,29 46 8 hours,53 10 hours10 and 24 hours 22 25 28 48 51. In other studies, the time for completing the microscopy was given in relation to the receipt time in the laboratory, and it ranged between 1 hour,11 18 30 31 33 35 2 hours,12 13 16 19 34 3 hours58 and 4 hours after receipt 21 24 62. In some of the studies, there was only a generic statement that urines had been tested without much delay9 17 27 38 39 50 54 56 65 or no clear statements 14 15 23 26 36 37 40–45 49 55 57…”
Section: Applicability Of the Validation Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with proteinuria, the "gold standard" for pathologic casts is the microscopic urinalysis of fresh urine by an experienced technician or nephrologist, and the results of urinary cell counters are not sensitive if renal disease is suspected. 7,8 Jiang et al 7 reported that compared with microscopy, the sensitivity for casts of the UF-1000i was only 69.8% and the machine could not differentiate between the various types of casts. Altekin et al 8 also reported that the sensitivity of the IQ-200 (IRIS International, Chatsworth, CA) for pathologic casts was low, only 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Altekin (24) stated that reducing the error rate could be achieved by cross-checking the analyzers ' result with dipstick data, such as RBC vs. BLD, and checking the samples containing crystals using microscopy. Our fi ndings provide further support that crystal and BLD are involved ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%